A Survey of the Effectiveness Model of College English Teachers' Classroom Discourse Based on Computer Assisted Technology from the Perspective of Speech Act Theory. Issue 3 (October 2020) - Nie, Ying
Abstract: Questioning in classroom is a part of the teachers' discourse and one of the most frequent and essential teaching skills used by teachers. Questioning can promote thinking, emphasize key points, stimulate engagement, control and test the learning situation of students. Questioning by teachers in classroom is different from that in our daily conversation. The purpose is not just to acquire information but to achieve pragmatic purposes at a deeper level. Hence, questioning by teachers is essentially a speech act with the specific pragmatic characteristics. This article uses the speech act theory, the questionnaire survey and interviews of computer-assisted technology to investigate the speech act of teachers asking questions, which provides a new perspective for understanding teachers' classroom discourse effectiveness model. In this way, teachers and students can make better use of language to achieve the purpose of communication.